Time, Materiality, and History in UK-Based Interfaith Solidarity Work - Egorova, Yulia (Material religion, 2024)
In this paper, building upon ethnographic fieldwork conducted among members of one initiative of Jewish-Muslim dialogue in the UK, I discuss how my interlocutors thematize the temporal dimension of anti-minority discrimination and perceive remaining historical material heritage associated with it. Using the example of problematic artifacts pertaining to mediaeval Lincoln, such as the so-called “shrine of Little Hugh,” I discuss how in engaging the memory of traumatic past events in Jewish history activists of inter-faith dialogue reflect on their current conditions of minoritization and attempt a projection of their communities’ lives in the UK in the future. I also borrow insight from the presentist theoretical framework in anthropology of time to highlight the impact my interlocutors’ life histories have had on the way they relate to and conceptualize their own and other minoritized groups’ histories and imagine their personal and collective futures based on their experiences in the present. I suggest that in these reflections, narratives of positive historical trajectories in the minority experience sit alongside an anticipation of multiple possible futures, some inflected with anxiety about a repetition of difficult pasts, others imbued with a vision connecting the past, present and future of minoritized communities into a common presence.